Magnetic Properties of Arrays of Nickel Nanowires Embedded in Alumina Nanoholes - Kyu Song, Chul; Kim, Dha-Hae; Yoo, So-Yeon; Jang, Se-Na; Hun Huh, Seung (Asian Journal of Chemistry, 2014)
Arrays of nickel nanowires were produced by electrochemical deposition of nickel ions onto the array of alumina nanoholes. The diameter and length of the nickel nanowires are 70-80 and 3-7 mm, respectively. The nickel nanowires had ferromagnetism and shape anisotropy to the parallel and perpendicular direction. Importantly, only parallel direction of nickel nanowires has drastic change of coercivities at 50 K, which is different from the reported result. Phase-transition like behaviour at 50 K is explained by three factors of magnetoeleastic effect, degree of thermal fluctuation of magnetic spin moments and shape anisotropy.